Utility of low-cost recreational-grade echosounders in imaging and characterizing bubbly coastal submarine groundwater discharge - Mary Rose P. Gabuyo; Fernando P. Siringan (Journal of Hydrology X, 2022)
Despite the growing knowledge on the significance of submarine groundwater discharge (SGD), mapping its occurrence is a continuing challenge. This study explores the capability and applicability of low-cost, off-the-shelf, recreational-grade echosounders (RGESs) to image different types and locate point sources of bubbly coastal SGD. Standard and systematic methodologies for efficient imaging and processing were established. The use of RGES was validated using a research-grade side scan sonar (RGSSS), continuous resistivity profiling, conductivity-temperature-depth casting, and MantaCam and SCUBA diving surveys. Lower frequencies (77/83 kHz) of RGESs showed more distinct acoustic signatures of bubbly SGD, as these were nearly the same as the effective resonance frequency of the bubbles. The clusters of bubbly discharges have higher backscatter strength than the water column noise, resulting in the definitive and convenient manual detection of SGD features. Hence, showing more accurate point sources of SGD. Three types of known SGD occurrence were identified and characterized based on acoustic behavior and spatial distribution: 1) sparse, discrete and sporadic discharge over wide area, 2) curtain, high and continuous bubble concentrations from widespread discharge, and 3) spring, direct bubble discharge from intense seafloor degassing at a single point source. These results showed that RGES provides a good alternative for more efficient and cost-effective preliminary coastal SGD works. Additional research on areas with water-dominated discharge but no bubbling is recommended.